Coumarino-12-crown-4 bearing phthalocyanine photosensitizers for singlet oxygen production - (:unkn) unknown (ELSEVIER SCIENCE SA, 2011)
The synthesis, characterization, photophysical and photochemical properties of the new metal-free and zinc (II) phthalocyanines tetra-substituted at the peripheral (complexes 3a and 3b) and non-peripheral (complexes 4a and 4b) positions with 7,8-(12-crown-4)-3-(4-oxyphenyl)coumarin groups are reported for the first time. The new compounds have been characterized by elemental analysis, FT-IR, H-1 NMR, electronic spectroscopy and mass spectra. General trends are described for photodegradation, singlet oxygen and fluorescence quantum yields, and fluorescence lifetimes of these compounds in dimethylsulphoxide (DMSO). Photophysical and photochemical properties of phthalocyanine complexes are very useful for photodynamic therapy (PDT) applications. The singlet oxygen quantum yields (phi(Delta)) ranged from 0.11 to 0.80 are indicating the potential of the complexes as photosensitizers in applications of PDT. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Coumarin; Crown ether; Singlet oxygen; Fluorescence; PHOTOCHEMICAL PROPERTIES; PHOTOPHYSICAL PROPERTIES; COPPER PHTHALOCYANINE; QUANTUM YIELDS; SUBSTITUENTS; COMPLEXES